Training on the Preparation of Manufacturing Financial Reports at a Business Entity Owned by Langgam Sako Village, Teluk Latak Village, Bengkalis Regency - Fachroh Fiddin Fiddin; Nurhazana Nurhazana; Husnul Muttaqin (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
This community service aims to provide understanding to village-owned enterprise managers on how the application of cost accounting is used in calculating production costs and making financial reports for manufacturing businesses. Through service activities, it is hoped that BUMDes managers have an understanding of recording production costs and manufacturing financial reports produced by production activities so that the recording of financial statements produced is by financial accounting standards. The method of service activities is carried out by providing an understanding of the concept of cost accounting in the process of preparing the cost of goods manufactured report and then practicing the use of accounting software for manufacturing businesses to record and make reports on the cost of production and manufacturing financial reports at Village Owned Enterprises in Teluk Latak Village, Regency Bengkalis